Interferensi Bahasa Anak Migran Desa Kasiyan Timur Kecamatan Puger - Nuris Setiawan (Journal on Education, 2024)
Language interference is a language error made by a community or group by inserting and mixing one language into another. Migrant children are children born to migrants from outside the area. East Kasiyan Village is a village that has a community with various languages, namely Madurese and Javanese, but the language that is more dominantly used by the community is Madurese. The problems that arise from this background are how the form of language interference of migrant children in East Kasiyan village, Puger District, and what are the factors that influence the language interference of migrant children in East Kasiyan village, Puger District. The purpose of this study was to describe the forms of language interference of migrant children in East Kasiyan Village, Puger District and to explain the factors that influence the language interference of migrant children in East Kasiyan Village, Puger District. Forms of language interference of migrant children in East Kasiyan Village, Puger District. This type of research is descriptive qualitative. The target in this study were the migrant children of East Kasiyan Village. The research location was in Kasiyan Timur Village, Puger District, Jember Regency, from 27 March 2023 to 27 April 2023. Data collection techniques were observation, interviews, free-to-view viewing (SBLC), and recording. The instruments in the study were data collection instrument tables, data analysis instrument tables and informant interview instruments. The data in the study were analyzed using a qualitative descriptive analysis method, namely data collection, data reduction, data presentation, and drawing conclusions, using the differential linking technique (HBB). The results of data analysis show language interference spoken by migrant children in East Kasiyan Village, Puger District, Jember Regency. The forms of interference spoken by migrant children include morphological interference in the form of affixations and reduplications and syntactic interference in the form of words, phrases, clauses and sentences. Factors that influence language interference by migrant children include the bilingualism of speakers, the lack of loyalty to the use of the first language, the need for synonyms, being carried away by the habits of the mother tongue, the prestige of the language and the style of language.